1978
DOI: 10.1002/j.2164-4918.1978.tb05090.x
|View full text |Cite
|
Sign up to set email alerts
|

APGA Members' Measured Client and Organizational Commitments and Professional Orientation

Abstract: The purpose of this study was to explore the issue of which of the counselor's commitments-the client or the employing institution-was giuen priority when they conflict. Members from four APGA divisions were examined for differences in commitments, and relationships of certain demographics and experiential uariables to commitment were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…There seems to be a consistently demonstrated need for increased counselor exposure to the legal (Jagim et al, 1978) and ethical (McMillan & Shertzer, 1978;Shertzer & Morris, 1972;Tymchuk et al, 1980) issues involved in counseling. This study provides evidence of the need for additional preparation in these areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There seems to be a consistently demonstrated need for increased counselor exposure to the legal (Jagim et al, 1978) and ethical (McMillan & Shertzer, 1978;Shertzer & Morris, 1972;Tymchuk et al, 1980) issues involved in counseling. This study provides evidence of the need for additional preparation in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…behavioral alternative was available. In a subsequent study, Thus, counselors apparently do differ in their personal re-McMillan and Shertzer (1978) focused on counselor decision sponses to ethical conflicts, and the presence of clear legal guidemaking in conflicts between organizational and individual prior-lines may affect counselor behavior in such conflicts. Usually in ities and found that counselors turned to a personal (unwritten) these studies, the antecedents of counselor decisions were unrather than a professional standard in conflict situations.…”
mentioning
confidence: 96%
“…Speculating from data collected from a sample of American Personnel and Guidance Association (APGA) members, McMillian and Shertzer (1978) suggest that APGA members have adopted a basically middle-of-the-road position with respect to conflicting loyalties. That is, the members recognize the limitations placed on them by their employing institutions, but within those limitations, they are oriented toward their commitment to the client.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…It is suggested, first, that the APGA Ethical Standards be revised to include a clearer statement of the Association's positions on this issue of conflicting loyalties. If, indeed, counselors are adopting a middle-of-the-road posture with respect to conflicting loyalties (McMillian & Shertzer, 1978) and are adjusting their ethics to fit those of their employing organization (Smith, 1958), then it seems reasonable to speculate that the lack of a clear statement of the Association's stance may be a contributing factor. This is not to suggest, of course, that a statement of the Association's stance alone is sufficient remedy for counselor equivocation in matters of conflicting loyalties.…”
Section: A Literature Reviewmentioning
confidence: 99%